Improving the effects of drought priming against post-anthesis drought stress in wheat (Triticum aestivum L.) using nitrogen - Ullah, Attiq; Tian, Zhongwei; Xu, Libing; Abid, Muhammad; Lei, Kangqi; Khanzada, Anab; Zeeshan, Muhammad; Sun, Chuanjiao; Yu, Jinhong; Dai, Tingbo (Frontiers in Plant Science, 2022)
Water and nitrogen (N) deficiencies are the major limitations to crop production, particularly when they occur simultaneously. By supporting metabolism, even when tissue water capacity is lower, nitrogen and priming may reduce drought pressure on plants. Therefore, the current study investigates the impact of nitrogen and priming on wheat to minimize post-anthesis drought stress. Plant morphology, physiology, and biochemical changes were observed before, during, and after stress at the post-anthesis stage. The plants were exposed to three water levels, i.e., well watering (WW), water deficit (WD), and priming at jointing and water deficit (PJWD) at the post-anthesis stage, and two different nitrogen levels, i.e., N180 (N1) and N300 (N2). Nitrogen was applied in three splits, namely, sowing, jointing, and booting stages. The results showed that the photosynthesis of plants with N1 was significantly reduced under drought stress. Moreover, drought stress affected chlorophyll (Chl) fluorescence and water-related parameters (osmotic potential, leaf water potential, and relative water content), grain filling duration (GFD), and grain yield. In contrast, PJWD couple with high nitrogen treatment (N300 kg ha–1) induced the antioxidant activity of peroxidase (37.5%), superoxide dismutase (29.64%), and catalase (65.66%) in flag leaves, whereas the levels of hydrogen peroxide (H2O2) and superoxide anion radical (O2–) declined by 58.56 and 66.64%, respectively. However, during the drought period, the primed plants under high nitrogen treatment (N300 kg ha–1) maintained higher Chl content, leaf water potential, and lowered lipid peroxidation (61%) (related to higher activities of ascorbate peroxidase and superoxide dismutase). Plants under high nitrogen treatment (N300 kg ha–1) showed deferred senescence, improved GFD, and grain yield. Consequently, the research showed that high nitrogen dose (N300 kg ha–1) played a synergistic role in enhancing the drought tolerance effects of priming under post-anthesis drought stress in wheat.